(untitled) (Scientific journal of the Fergana State University, 2023)
Linear copolymers of methylacrylate and acrylic acid with different content of monomer units have been synthesized by classical radical copolymerization in dioxane solution and in the block. The composition of copolymers was determined. The relative activities of the monomers calculated by the methods of Fineman - Ross and Kelen -Tudos. It is shown that the activity of acrylic acid can vary depending on the medium in which copolymerization is carried out